2019
DOI: 10.1158/1078-0432.ccr-17-3572
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I and Pharmacokinetic Study of Oral Dabrafenib in Children and Adolescent Patients with Recurrent or Refractory BRAF V600 Mutation–Positive Solid Tumors

Abstract: Purpose: The 2-part, phase I/IIa, open-label study (NCT01677741) sought to determine the safety, tolerability, pharmacokinetics, and preliminary activity of dabrafenib in pediatric patients with advanced BRAF V600-mutated cancers.Patients and Methods: This phase I dose-finding part treated patients ages 1 to <18 years with BRAF V600 mutationpositive tumors with oral dabrafenib 3 to 5.25 mg/kg/day to determine the RP2D based on safety and drug exposure target.Results: Between May 2013 and November 2014, 27 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 34 publications
2
85
0
Order By: Relevance
“…Our study found a high proportion of objective radiographic responses that were durable, with 1 CR, 5 PRs, and 13 SDs as the centrally-reviewed best responses on therapy. The recently reported phase I/IIa experience with the BRAF V600E inhibitor dabrafenib in children with recurrent pediatric low grade glioma reported 1 CR, 13 PR, 11 SD and two progressive diseases as best responses in a cohort of 32 patients [12,13]. This is of particular interest as both drugs have been shown to have poor CNS penetration in animal models [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a high proportion of objective radiographic responses that were durable, with 1 CR, 5 PRs, and 13 SDs as the centrally-reviewed best responses on therapy. The recently reported phase I/IIa experience with the BRAF V600E inhibitor dabrafenib in children with recurrent pediatric low grade glioma reported 1 CR, 13 PR, 11 SD and two progressive diseases as best responses in a cohort of 32 patients [12,13]. This is of particular interest as both drugs have been shown to have poor CNS penetration in animal models [14].…”
Section: Discussionmentioning
confidence: 99%
“…Novel therapeutic options are thus urgently needed. Recent studies have demonstrated safety and remarkable efficacy of BRAF [73–78] and MEK [78,79] inhibition in patients with BRAF ‐mutated or BRAF wildtype histiocytic neoplasms, respectively. Moreover, dramatic responses to selective inhibition of RET (Selpercatinib) or ALK (Crizotinib) have been observed in two patients with histiocytic neoplasms driven by rare rearrangements involving one of these genes [10], and high response rates have been described in ECD patients treated with the mTOR inhibitor Sirolimus [80].…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of dabrafenib was 2 mg/kg according to dose escalation and dose limiting toxicity (DLT) evaluation in a phase I/II study on dabrafenib in children with refractory/resistant BRAF V600E solid tumors [11], and for the treatment of pediatric BRAF V600E mutated high grade gliomas [12], dabrafenib was administered orally once every 12 hours. The general duration of the course of dabrafenib treatment was 6 months to 1 year, adjusted according to disease assessment and patient tolerance to the drug.…”
Section: Therapeutic Regimenmentioning
confidence: 99%
“…The most common adverse events of dabrafenib reported in the literature are skin-related toxic effects (including maculopapular rash, skin pain, and severe events, including squamous cell carcinoma and keratocanthoma), fever, fatigue, arthralgia, etc [11].…”
Section: Adverse Effects and Treatmentsmentioning
confidence: 99%